2018
DOI: 10.1177/0021998318788915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heterogeneity at the fiber–matrix scale on predicted free-edge stresses for a [0°/90°]s laminated composite subjected to uniaxial tension

Abstract: The effect of the free-edge on the interlaminar stresses that develop in a thin-ply [0°/90°]s laminated composite under uniaxial tension was explored using finite element models that directly modeled the random heterogeneous microstructure and a model that treated the plies as homogeneous, orthotropic materials. The deformed cross-sections were compared for the two cases, showing that the homogeneous model generally captured the displacement field well but the heterogenous model exhibited local perturbations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…The complex stress pattern was due to the interactions of fibers near the interface. As noted in McLendon and Whitcomb 11 and Ballard and Whitcomb, 15 compressive stresses form when fibers come into close proximity. Ballard and Whitcomb 15 also observed that tensile stress concentrations form near matrix pockets.…”
Section: Effect Of Modeling Discrete Fibers and Matrixmentioning
confidence: 75%
“…The complex stress pattern was due to the interactions of fibers near the interface. As noted in McLendon and Whitcomb 11 and Ballard and Whitcomb, 15 compressive stresses form when fibers come into close proximity. Ballard and Whitcomb 15 also observed that tensile stress concentrations form near matrix pockets.…”
Section: Effect Of Modeling Discrete Fibers and Matrixmentioning
confidence: 75%
“…For many years, researchers have used classical laminate theories, finite difference models, and finite element analysis (FEA) to characterize the effects of the free edge for various types of layup with great success. 21 Consequently, some researchers have employed multiscale strategies to capture the effects of fibers in critical regions. 22 During the manufacturing and machining (e.g., curing, cutting, terming, and drilling) processes of these composites, there will be some machine damage and free-edge formation on the composites, which in turn reduce the overall mechanical properties through associated inter-laminar tension and shear stresses; they are also very detrimental to the structural applications of composites in those industries due to premature failure.…”
Section: Introductionmentioning
confidence: 99%
“…36 developed a micromechanical damage model for failure prediction in laminated composites. In another work, Ballard and Whitcomb 37 considered a multi-scale model to investigate the micro-scale free-edge effect in laminated composites. Moreover, Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, to consider the effect of micromechanics of the damage, many studies carried out modeling in micro-scale. [36][37][38][39][40][41] Using multi-scale modeling, Mohammadi et al 36 developed a micromechanical damage model for failure prediction in laminated composites. In another work, Ballard and Whitcomb 37 considered a multi-scale model to investigate the micro-scale free-edge effect in laminated composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation